Doktrin Penciptaan dalam Alkitab dan Kaitannya dengan Tanggung Jawab Manusia terhadap Alam Serta Relevansinya bagi Gereja (International Forum of Researchers and Lecturers, 2025)
This article aims to explore how the relationship between God and humans (Creator and creation) in relation to their responsibilities as humans to try to keep the earth free from damage that will certainly harm humans themselves. Humans as God's partners on earth are also given a mandate to keep the earth good as in the creation narrative that everything created by God is truly very good. It turns out that the narrative was ignored and turned bad. Humans who were given reason by God, turned out not to use their reason well. Humans who were given a mandate to protect nature well, instead exploited nature arbitrarily. So, nature cannot be friendly with humans, so that lately we have felt the very high heat of the sun and it stings the skin sharply. It is very clear that the heat of the sun that shines is not like the heat that was some time ago not as hot as recently. Perhaps this is the cause of global warming. The world is getting hotter because the ozone layer can no longer withstand the hot and dangerous ultraviolet rays (sun). There is no doubt, global warming will be a universal disaster that will slowly but surely destroy this